Consumption of selected groups of food products by medical and non-medical students during the Covid-19 pandemic - Elżbieta Szczepańska; Barbara Janota; Kamil Mąkosza; Natalia Zięba; Marika Wlazło; Martyna Czapla (Roczniki Panstwowego Zakladu Higieny, 2022)
Background. A properly balanced diet should provide multiple valuable nutrients necessary for the proper functioning of the body through the proper frequency of consuming food products that are their source. This is particularly important during the pandemic when there is a need to support the immune system. Objective. The aim of the study was to assess the frequency of consumption of selected groups of food products and to determine whether this frequency differs among medical and non-medical students in the period before and during the COVID-19 pandemic. Material and methods. The study was conducted among 435 Polish and Turkish students using an original questionnaire. The proper study was preceded by a pilot study in 40 participants.The Wilcoxon test was used to assess the differences in the frequency of consumption of selected groups of products among medical and non-medical students both during and before the pandemic. A value of p<0.05 was considered statistically significant. Results. Significant differences were observed in the frequency of consumption of: sweets (p=0.02 among medical students), salty snacks (p=0.03 among both groups of students), fast food products (p=0.00 among medical and p=0.01 among non-medical students) and energy drinks (p=0.02 among medical and p=0.00 among non-medical student) in the analysed periods of time before and during the COVID-19 pandemic. Conclusions. The study showed that during the pandemic, the frequency of food products consumption in the study groups of students from medical and non-medical faculties is mostly satisfactory. There were significant differences in the frequency of consumption of sweets, salty snacks, fast food products and energy drinks in both groups of students.